2020
DOI: 10.1177/1054773820980162
|View full text |Cite
|
Sign up to set email alerts
|

Distorted Memories and Related Factors in ICU Patients

Abstract: This study aimed to examine the relationship between memory status of and factors related to patients in the intensive care unit (ICU) using a cross-sectional study design. Participants were adult patients who were admitted to the general ICUs for more than 48 hours. One week after ICU discharge, a survey on memory distortion was conducted. Overall, 133 patients were included, of whom 51.1% reported distorted memories. Among them, 15.0% had memory loss; 48.1% had unrealistic experiences; 27.8% recalled confusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In their study, Edeer et al ( 9 ) determined that with the prolongation of the length of stay in the intensive care unit, intensive care experiences were adversely affected. Fukuda et al revealed that one week after discharge from the general intensive care unit, 15.0% of patients had memory loss and 48.1% had unrealistic experiences ( 14 ). Another study revealed that patients with a long length of stay had more pessimistic experiences ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Edeer et al ( 9 ) determined that with the prolongation of the length of stay in the intensive care unit, intensive care experiences were adversely affected. Fukuda et al revealed that one week after discharge from the general intensive care unit, 15.0% of patients had memory loss and 48.1% had unrealistic experiences ( 14 ). Another study revealed that patients with a long length of stay had more pessimistic experiences ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that some patients experience depression, anxiety, and intensive care unit syndrome due to the negative conditions of intensive care units and negative experiences ( 6 , 12 , 13 ). Furthermore, it is reported that some patients remember the confusion, panic, anxiety, and discomfort experienced during their stay in the intensive care unit ( 14 ). Intensive care experiences can leave negative traces on patients, and patients want to leave these traces in the past ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate opioid use may prevent cognitive decline after ICU discharge and can improve comfort and emotional stability in critically ill patients (Fernández-Gonzalo et al, 2020;Fukuda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when midazolam is used, patients are prone to deep sedation and delusional memories (Samuelson et al., 2006). Appropriate opioid use may prevent cognitive decline after ICU discharge and can improve comfort and emotional stability in critically ill patients (Fernández‐Gonzalo et al., 2020; Fukuda et al., 2020). Thus, pain assessment and maintenance of light sedation with appropriate analgesics can also be useful in relieving patients from long‐term pain and discomfort, preventing distorted memories and forming consistent memories.…”
Section: Discussionmentioning
confidence: 99%